2018
DOI: 10.5152/tjg.2018.17752
|View full text |Cite
|
Sign up to set email alerts
|

Results of positive proximal margin after resection for hilar cholangiocarcinoma: An analysis of 42 cases

Abstract: Background/Aims: Hilar cholangiocarcinoma (HC) is a tumor that invades the confluence of the left and right hepatic bile ducts. Surgery is the definitive treatment but is also technically demanding. Here, we report our experience on 42 patients who underwent surgical resection for HC. The aim of the present study was to evaluate the margin status of resected specimens on frozen sections and the impact of R1 resection margin on survival. Materials and Methods: A total of 42 patients with HC who underwent surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, several authors have suggested that patients whose positive margins contain carcinoma could survive beyond 5 years. Volkan Öter et.al [25] reported that the survival of patients with tumor positive margins was not found to be worse than those with tumor negative margins. Further large volume prospective studies are required to identify the impact of positive proximal margins on the survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, several authors have suggested that patients whose positive margins contain carcinoma could survive beyond 5 years. Volkan Öter et.al [25] reported that the survival of patients with tumor positive margins was not found to be worse than those with tumor negative margins. Further large volume prospective studies are required to identify the impact of positive proximal margins on the survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the negative surgical margin (R0) cannot be achieved, and the tumor continues as R1 or R2, removal of the dissected tissue and tumor may become necessary. Disruption of the bleeding of the dissected bile ducts, enlargement of the hepatectomy limit, increased risk of developing liver failure, and comorbidities may remain in the operation drainage or palliative resection stage [17,18]. In some cases where the negative surgical margin is provided, segmental bile duct resection is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate was reported as 11-45% in patients undergoing curative resection and 0-23% in patients with R1 resection in the literature [10]. Many studies are stating that there is no difference between surgery with negative surgical margin and positive surgical margin, and also, some studies state that palliative resection positively affects survival [8,18]. The Mayo Clinic has reported promising results in 1, 3, and 5-year survival 92%, 82%, and 82%, respectively, in the series of liver transplantation after neoadjuvant therapy in selected hilar cholangiocarcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical liver resection is the standard procedure for HCCA. To achieve R0 resection, it is recommended to carry out intraoperative frozen sections to confirm negative proximal and distal bile duct resection margins ( 5 8 ).…”
Section: Indications and Treatment Principles For Laparoscopic Radical Resection Of Hccamentioning
confidence: 99%